2016
DOI: 10.1631/jzus.b1500199
|View full text |Cite
|
Sign up to set email alerts
|

Association of VIPR-1 gene polymorphisms and haplotypes with egg production in laying quails

Abstract: Abstract:The laying quail is a worldwide breed which exhibits high economic value. In our current study, the vasoactive intestinal peptide receptor-1 (VIPR-1) was selected as the candidate gene for identifying traits of egg production. A single nucleotide polymorphism (SNP) detection was performed in 443 individual quails, including 196 quails from the H line, 202 quails from the L line, and 45 wild quails. The SNPs were genotyped using a polymerase chain reaction-restriction fragment length polymorphism (PCR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The Hpy CH4 IV site was significantly deviated from HWE ( P < 0.05) in SV, and was consistent with HWE ( P > 0.05) in FG. Pu et al (2016) reported that the detection of 2 SNPs (G373T and A313G) in the VIPR-1 gene of the 3 quail strains was similar to the results of this study.
Figure 1 Detection of PCR amplification products and digestion products at the Bsr D I and Hpy CH4 IV sites of VIPR-1 gene.
…”
Section: Results and Disscusionsupporting
confidence: 89%
See 2 more Smart Citations
“…The Hpy CH4 IV site was significantly deviated from HWE ( P < 0.05) in SV, and was consistent with HWE ( P > 0.05) in FG. Pu et al (2016) reported that the detection of 2 SNPs (G373T and A313G) in the VIPR-1 gene of the 3 quail strains was similar to the results of this study.
Figure 1 Detection of PCR amplification products and digestion products at the Bsr D I and Hpy CH4 IV sites of VIPR-1 gene.
…”
Section: Results and Disscusionsupporting
confidence: 89%
“…The restriction enzyme system was 10 μL: 1 μL 1× buffer, 7.5 μL PCR product, restriction enzyme 0.5 μL Bsr D I (5 U/μL) or Hpy CH4 IV (10 U/μL), 1 μL ddH 2 O. After centrifugation, the Bsr D I system was digested overnight in an incubator at 37°C, while Hpy CH4 IV system was digested in an incubator at 65°C for 1 h ( Pu et al, 2016 ). The enzyme products were detected by 1% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the recorded LBW values in the Brown-line were decreased at 9 th to 12 th weeks of the experiment. These reduced LBW values may be related to the high efforts performed by this line to produce a higher number of eggs (23). For this reason, larger amounts of the consumed food were utilized in egg production and maintenance requirements instead (29).…”
Section: Table 1 Effect Of the Line Of Japanese Quails On Live Body Weight (Lbw)mentioning
confidence: 99%
“…These observations may refer to a considerable correlation between IGF2 function and egg production. Likewise, several candidate genes are increasingly being reported to be associated with production traits in quails [ 26 28 ]. For this reason, the genetic variations within this critical gene may bring several alterations for productive performance in quail populations.…”
Section: Discussionmentioning
confidence: 99%